Diaphragm neuromuscular transmission failure in aged rats - Fogarty, Matthew J.; Gonzalez Porras, Maria A.; Mantilla, Carlos B.; Sieck, Gary C. (Journal of neurophysiology, 2019)
In aging Fischer 344 rats, phrenic motor neuron loss, neuromuscular junction abnormalities, and diaphragm muscle (DIAm) sarcopenia are present by 24 mo of age, with larger fast-twitch fatigue-intermediate (type FInt) and fast-twitch fatigable (type FF) motor units particularly vulnerable. We hypothesize that in old rats, DIAm neuromuscular transmission deficits are specific to type FInt and/or FF units. In phrenic nerve/DIAm preparations from rats at 6 and 24 mo of age, the phrenic nerve was supramaximally stimulated at 10, 40, or 75 Hz. Every 15 s, the DIAm was directly stimulated, and the difference in forces evoked by nerve and muscle stimulation was used to estimate neuromuscular transmission failure. Neuromuscular transmission failure in the DIAm was observed at each stimulation frequency. In the initial stimulus trains, the forces evoked by phrenic nerve stimulation at 40 and 75 Hz were significantly less than those evoked by direct muscle stimulation, and this difference was markedly greater in 24-mo-old rats. During repetitive nerve stimulation, neuromuscular transmission failure at 40 and 75 Hz worsened to a greater extent in 24-mo-old rats compared with younger animals. Because type IIx and/or IIb DIAm fibers (type FInt and/or FF motor units) display greater susceptibility to neuromuscular transmission failure at higher frequencies of stimulation, these data suggest that the age-related loss of larger phrenic motor neurons impacts nerve conduction to muscle at higher frequencies and may contribute to DIAm sarcopenia in old rats. NEW & NOTEWORTHY Diaphragm muscle (DIAm) sarcopenia, phrenic motor neuron loss, and perturbations of neuromuscular junctions (NMJs) are well described in aged rodents and selectively affect FInt and FF motor units. Less attention has been paid to the motor unit-specific aspects of nerve-muscle conduction. In old rats, increased neuromuscular transmission failure occurred at stimulation frequencies where FInt and FF motor units exhibit conduction failures, along with decreased apposition of pre- and postsynaptic domains of DIAm NMJs of these units.